Kinds of Determinism in Science - Alexander Maar (Principia: An International Journal of Epistemology)
Determinism is a doctrine or assumption best defined in the realm of the natural sciences. In this paper I explain in detail the four senses of determinism, from the most fundamental metaphysical sense, to the most complex epistemic (predictive) sense. I take as a starting point the analysis of determinism offered by Stephen Kellert. Each of these senses is then expounded and commented with a view to explore some of the implications of each of them in theoretical physics. The most important of my tasks in this paper is to differentiate between the metaphysical and epistemic consequences of the deterministic assumption. My objective is to show that determinism as an ontological tenet is capable of withstanding criticism, even though predictive determinism is likely to be false.